PENGARUH DANA ALOKASI UMUM (DAU) DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH PROVINSI JAWA BARAT (Studi Kasus Pada Kota di Provinsi Jawa Barat Periode 2017-2020) - Fadhiilah, Rifda; Widiastuty, Tri (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2023)
The objective of this study is to determine how the General Allocation Fund and Economic Growth affect the West Java Province's level of regional financial independence between 2017 and 2020. The nine cities in the West Java Province from 2017 to 2019 made up the study's population. Purposive sampling was used to gather the samples for the study, resulting in the selection of nine districts/cities. Secondary data is the kind of data that is used. Economic growth and general allocation funds are the independent variables that are considered. The degree of financial independence in a region is the dependent variable that is being employed. Panel data regression and descriptive statistics are the methods of data analysis that are employed. The study's findings indicate that: (1) Economic Growth has a partial impact on the level of regional financial independence; (2) General Allocation Funds has a partial impact on the level of regional financial independence; and (3) Both Economic Growth and General Allocation Funds have no concurrent effect on the level of regional financial independence.